Epidemiology of blaCTX-M-Positive Salmonella Typhimurium From Diarrhoeal Outpatients in Guangdong, China, 2010–2017 - Jiang, Qi; Ke, Bi-xia; Wu, De-shu; Wang, Dong; Fang, Liang-xing; Sun, Ruan-yang; Wang, Min-ge; Lei, Jing-er; Shao, Zheng; Liao, Xiao-ping (Frontiers in Microbiology, 2022)
Salmonella enterica can lead to intestinal diarrhea, and the emergence and spread of cephalosporin-resistant Salmonella have brought great challenges to clinical treatment. Therefore, this study investigated the prevalence and transmission of blaCTX-M genes among S. Typhimurium from diarrhoeal outpatients in Guangdong, China, from 2010 to 2017. A total of 221 blaCTX-M-positive isolates were recovered from 1263 S. Typhimurium isolates from the faecal samples of diarrhoea patients in 45 general hospitals from 11 cities. The most popular CTX-M gene was blaCTX-M-55 (39.6%, 72/182) in the CTX-M-1 group, followed by blaCTX-M-14 (22.5%, 41/182) and blaCTX-M-65 (19.2%, 35/182) in the CTX-M-9 group. The isolates that carried blaCTX-M-9G had significantly higher resistance rates to multiple antibacterials compared with blaCTX-M-1G (p < 0.01). Meanwhile, PFGE analysis not only showed the clonal transmission of blaCTX-M-55/14/65-positve isolates of diarrhoeal outpatients’ origins from different hospitals in Guangdong province, but also the characteristic of blaCTX-M-55/14/65-positve isolates’ bacterial persistence. Multilocus sequence typing (MLST) analysis indicated that these S. Typhimurium isolates possessed ST34 and ST19. Furthermore, genomic Beast phylogenomic analysis provided the evidence of a close relationship of blaCTX-M-positive S. Typhimurium isolates between the outpatients and pork. Most blaCTX-M-55/14/65 genes were transmitted by non-typeable or IncI1/IncFII/IncHI2 plasmids with the size of ranging from 80 to 280 kb. Moreover, whole-genome sequencing (WGS) analysis further revealed that blaCTX-M-55/14/65 coexisted with other 25 types of ARGs, of which 11 ARGs were highly prevalent with the detection rates >50%, and it first reported the emergence of blaTEM-141 in S. Typhimurium. This study underscores the importance of surveillance for blaCTX-M-positive microbes in diarrhea patients.